DAMPAK AGROWISATA KOPI TERHADAP FAKTOR SOSIAL EKONOMI PETANI DI DESA COLOL KECAMATAN LAMBA LEDA TIMUR KABUPATEN MANGGARAI TIMUR - Fenansius Aldi Gou; Fredrik L. Benu; Ernantje Hendrik (Journal Education and Government Wiyata, 2026)
Agritourism development is a rural development strategy that integrates the agricultural and tourism sectors to increase the added value of local commodities and community welfare. Colol Village, located in East Lamba Leda District, East Manggarai Regency, is known as one of the prominent centers for Arabica coffee production in East Nusa Tenggara Province, which has begun to develop as an agritourism destination. This study aims to analyze the characteristics of coffee agritourism development, the level of coffee farming income, and the socio-economic impacts of agritourism development on farmers. This research employed a quantitative approach using a survey method involving 70 coffee farmers selected through purposive sampling. Data collection was conducted through observation, in-depth interviews, and questionnaire distribution. Data were analyzed using descriptive analysis, farm income analysis, multiple linear regression, and path analysis using SPSS software. The results showed that coffee agritourism development contributes positively to improving the community's socio-economic conditions. The coefficient of determination ($R^2$) of 56.2% indicates that a substantial portion of the variation in farmers' income is explained by variables such as farmer participation, additional business activities, agritourism supporting activities, and job creation. Partially, farmer participation (Sig. 0.002) and additional businesses resulting from agritourism (Sig. 0.012) have a positive and significant effect on increasing farmers' income, whereas tourism area sanitation activities and job creation have not shown a significant effect. Beyond increasing farm household income, agritourism development also fosters community cooperation, improves environmental quality, diversifies economic ventures, and strengthens the identity of Colol Village as a coffee agritourism region. Thus, community-based agritourism development serves as a viable strategy for sustainable rural economic development.